Small molecule AZD4635 inhibitor of A2AR signaling rescues immune cell function including CD103+ dendritic cells enhancing anti-tumor immunity. Issue 2 (29th July 2020) - Borodovsky, Alexandra; Barbon, Christine M; Wang, Yanjun; Ye, Minwei; Prickett, Laura; Chandra, Dinesh; Shaw, Joseph; Deng, Nanhua; Sachsenmeier, Kris; Clarke, James D; Linghu, Bolan; Brown, Giles A; et al.
Abstract : Accumulation of extracellular adenosine within the microenvironment is a strategy exploited by tumors to escape detection by the immune system. Adenosine signaling through the adenosine 2A receptor (A2A R) on immune cells elicits a range of immunosuppressive effects which promote tumor growth and limit the efficacy of immune checkpoint inhibitors. Preclinical data with A2A R inhibitors have demonstrated tumor regressions in mouse models by rescuing T cell function; however, the mechanism and role on other immune cells has not been fully elucidated. Methods: We report here the development of a small molecule A2A R inhibitor including characterization of binding and inhibition of A2A R function with varying amounts of a stable version of adenosine. Functional activity was tested in both mouse and human T cells and dendritic cells (DCs) in in vitro assays to understand the intrinsic role on each cell type. The role of adenosine and A2A R inhibition was tested in DC differentiation assays as well as co-culture assays to access the cross-priming function of DCs. Syngeneic models were used to assess tumor growth alone and in combination with alphaprogrammed death-ligand 1 (αPD-L1). Immunophenotyping by flow cytometry was performed to examine global immune cell changes upon A2A R inhibition. Results: We provide the first report of AZD4635, a novel small molecule A2A R antagonist which inhibits downstream signaling and increases T cell function as well as a novel mechanism of enhancing antigen presentation by CD103 + DCs. The role of antigen presentation by DCs, particularly CD103 + DCs, is critical to drive antitumor immunity providing rational to combine a priming agent AZD4635 with check point blockade. We find adenosine impairs the maturation and antigen presentation function of CD103 + DCs. We show in multiple syngeneic mouse tumor models that treatment of AZD4635 alone and in combination with αPD-L1 led to decreased tumor volume correlating with enhanced CD103 + function and T cell response. We extend these studies into human DCs to show that adenosine promotes a tolerogenic phenotype that can be reversed with AZD4635 restoring antigen-specific T cell activation. Our results support the novel role of adenosine signaling as an intrinsic negative regulator of CD103 + DCs maturation and priming. We show that potent inhibition of A2A R with AZD4635 reduces tumor burden and enhances antitumor immunity. This unique mechanism of action in CD103 + DCs may contribute to clinical responses as AZD4635 is being evaluated in clinical trials with IMFINZI (durvalumab, αPD-L1) in patients with solid malignancies. Conclusion: We provide evidence implicating suppression of adaptive and innate immunity by adenosine as a mechanism for immune evasion by tumors. Inhibition of adenosine signaling through selective small molecule inhibition of A2A R using AZD4635 restores T cell function via an internal mechanism as well as tumor antigen cross-presentation by CD103 + DCs resulting in antitumor immunity.